STRATEGI PENGEMBANGAN USAHA BAWANG GORENG CRISPY DONGGALA DI INDUSTRI RUMAH TANGGA MANDIRI JAYA DI DESA LABUAN PANIMBA KECAMATAN LABUAN KABUPATEN DONGGALA - Febrianti, Ila; Effendy, Effendy; Nurdin, Muh. Fahrudin (AGROTEKBIS : JURNAL ILMU PERTANIAN (e-journal), 2024)
This study examined the internal and external factors influencing the development of the "Mandiri Jaya" crispy fried onion business, established by Mrs. Irawati in 2016. The goal is to identify these factors and formulate strategies for developing the Donggala Crispy Fried Onion business within the Mandiri Jaya Home Industry. The analysis revealed that the most effective strategy is the Strengths-Opportunities (SO) approach, which influences the business's strengths to capitalize on opportunities. The calculated strength factor is 2.52, and the opportunity factor is 2.30, both of which exceed the weakness factor (0.83) and threat factor (0.78). This results in internal and external factor comparisons of 1.96 (X-axis) and 1.53 (Y-axis), respectively, indicating a strong potential for business development through strategic alignment.